Arthroscopic Treatment of Shoulder Instability With Glenoid Bone Loss Using Distal Tibial Allograft Augmentation: Safety Profile and Short-Term Radiological Outcomes. Issue 5 (21st May 2018) - Amar, Eyal; Konstantinidis, George; Coady, Catherine; Wong, Ivan H.
Background: The results of arthroscopic anterior labral repair have demonstrated high failure rates in patients with significant glenoid bone loss. Several reconstruction procedures using a bone graft have been developed to overcome bone loss. Purpose: The primary objective of this study was to generate a safety profile for arthroscopic anatomic glenoid reconstruction using a distal tibial allograft. The secondary objective was to evaluate the radiological outcomes of patients who underwent this procedure. Study Design: Case series; Level of evidence, 4. Methods: This retrospective review included the medical charts and diagnostic images of 42 consecutive patients who underwent arthroscopic shoulder stabilization by means of capsule-labral reattachment and bony augmentation with a distal tibial allograft. The safety profile was measured by detecting intraoperative or postoperative complications, including neurovascular (nerves and blood vessels) injuries, bleeding, infections, and dislocations. A radiological evaluation was conducted by assessing computed tomography (CT) scans obtained preoperatively and at approximately 6 months postoperatively. Results: A total of 42 patients (29 male, 13 female) with a mean age of 26.73 ± 9.01 years were included. An excellent safety profile was observed, with no intraoperative complications, neurovascular injuries, adverse events, bleeding, or infections. CT bone scans were obtained for 31 patients, and the mean follow-up for CT scanning (to measure resorption and union) was 6.31 ± 1.20 months (range, 6-7.5 months). There were no cases of nonunion or partial union. Thirteen patients (42%) had no resorption, whereas 13 (42%) and 5 (16%) patents had <50% and ≥50% resorption, respectively. Conclusion: Arthroscopic shoulder stabilization with distal tibial allograft reconstruction is a safe operative procedure with a minimal risk to neurovascular structures. Most patients had a healed allograft, but 16% of patients had ≥50% resorption on CT at 6 months. Studies with a longer follow-up are recommended for better assessment of the safety profile.